Implementasi UI UX Website Queen Shop Jkt Dengan Metode Design Thinking - Sabrina Qodri Nova; Rahmi Imanda, M.Kom. (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2023)
Queen Shop JKT is a bakery with a diverse menu. The problem experienced is the difficulty in financial management which is still done manually, making it prone to errors in recording. This research aims to develop a user-centered design method to meet the needs of the shop and introduce UI/UX to improve financial management on their website. Design Thinking is a creative problem-solving method, prioritizing user involvement, which consists of Empathize, Define, Ideate, Prototype, and Test stages. The test results confirmed that the implementation of the website UI/UX significantly improved the efficiency of Queen Shop JKT’s financial management. This was proven at the testing stage through usability testing on 7 respondents and obtained an average score of 85 using the System Usability Scale (SUS) technique. It can be interpreted that so far the website meets the needs of users.